# 99 questions/Solutions/17

### From HaskellWiki

< 99 questions | Solutions(Difference between revisions)

m (added another fold solution) |
|||

(2 intermediate revisions by 2 users not shown) | |||

Line 3: | Line 3: | ||

Do not use any predefined predicates. | Do not use any predefined predicates. | ||

− | Solution using take and drop: | + | Solution using <hask>take</hask> and <hask>drop</hask>: |

+ | |||

<haskell> | <haskell> | ||

split xs n = (take n xs, drop n xs) | split xs n = (take n xs, drop n xs) | ||

</haskell> | </haskell> | ||

− | Alternatively, we have the following recursive solution: | + | Or even simpler using <hask>splitAt</hask>: |

+ | |||

+ | <haskell> | ||

+ | split = flip splitAt | ||

+ | </haskell> | ||

+ | |||

+ | But these should clearly be considered "predefined predicates". Alternatively, we have the following recursive solution: | ||

+ | |||

<haskell> | <haskell> | ||

split :: [a] -> Int -> ([a], [a]) | split :: [a] -> Int -> ([a], [a]) | ||

Line 18: | Line 26: | ||

The same solution as above written more cleanly: | The same solution as above written more cleanly: | ||

+ | |||

<haskell> | <haskell> | ||

split :: [a] -> Int -> ([a], [a]) | split :: [a] -> Int -> ([a], [a]) | ||

Line 24: | Line 33: | ||

</haskell> | </haskell> | ||

− | Note that | + | A similar solution using foldl: |

+ | |||

+ | <haskell> | ||

+ | split :: [a] -> Int -> ([a], [a]) | ||

+ | split [] _ = ([], []) | ||

+ | split list n | ||

+ | | n < 0 = (list, []) | ||

+ | | otherwise = (first output, second output) | ||

+ | where output = foldl (\acc e -> if third acc > 0 then (first acc ++ [e], second acc, third acc - 1) else (first acc, second acc ++ [e], third acc)) ([], [], n) list | ||

+ | </haskell> | ||

+ | |||

+ | Note that for the above code to work you must define your own first, second, and third functions for tuples containing three elements like so: | ||

+ | |||

+ | <haskell> | ||

+ | first :: (a, b, c) -> a | ||

+ | first (x, _, _) = x | ||

+ | |||

+ | second :: (a, b, c) -> b | ||

+ | second (_, y, _) = y | ||

+ | |||

+ | third :: (a, b, c) -> c | ||

+ | third (_, _, z) = z | ||

+ | </haskell> | ||

+ | |||

+ | Another foldl solution without defining tuple extractors: | ||

+ | <haskell> | ||

+ | split :: [a] -> Int -> ([a],[a]) | ||

+ | split lst n = snd $ foldl helper (0,([],[])) lst | ||

+ | where helper (i,(left,right)) x = if i >= n then (i+1,(left,right++[x])) else (i+1,(left++[x],right)) | ||

+ | </haskell> |

## Revision as of 00:31, 24 December 2011

(*) Split a list into two parts; the length of the first part is given.

Do not use any predefined predicates.

Solution usingtake

drop

split xs n = (take n xs, drop n xs)

splitAt

split = flip splitAt

But these should clearly be considered "predefined predicates". Alternatively, we have the following recursive solution:

split :: [a] -> Int -> ([a], [a]) split [] _ = ([], []) split l@(x : xs) n | n > 0 = (x : ys, zs) | otherwise = ([], l) where (ys,zs) = split xs (n - 1)

The same solution as above written more cleanly:

split :: [a] -> Int -> ([a], [a]) split xs 0 = ([], xs) split (x:xs) n = let (f,l) = split xs (n-1) in (x : f, l)

A similar solution using foldl:

split :: [a] -> Int -> ([a], [a]) split [] _ = ([], []) split list n | n < 0 = (list, []) | otherwise = (first output, second output) where output = foldl (\acc e -> if third acc > 0 then (first acc ++ [e], second acc, third acc - 1) else (first acc, second acc ++ [e], third acc)) ([], [], n) list

Note that for the above code to work you must define your own first, second, and third functions for tuples containing three elements like so:

first :: (a, b, c) -> a first (x, _, _) = x second :: (a, b, c) -> b second (_, y, _) = y third :: (a, b, c) -> c third (_, _, z) = z

Another foldl solution without defining tuple extractors:

split :: [a] -> Int -> ([a],[a]) split lst n = snd $ foldl helper (0,([],[])) lst where helper (i,(left,right)) x = if i >= n then (i+1,(left,right++[x])) else (i+1,(left++[x],right))